Long-term biocompatibility, imaging appearance and tissue effects associated with delivery of a novel radiopaque embolization bead for image-guided therapy. (October 2016) - Sharma, Karun V.; Bascal, Zainab; Kilpatrick, Hugh; Ashrafi, Koorosh; Willis, Sean L.; Dreher, Matthew R.; Lewis, Andrew L.
Abstract: The objective of this study was to undertake a comprehensive long-term biocompatibility and imaging assessment of a new intrinsically radiopaque bead (LC Bead LUMI™) for use in transarterial embolization. The sterilized device and its extracts were subjected to the raft of ISO10993 biocompatibility tests that demonstrated safety with respect to cytotoxicity, mutagenicity, blood contact, irritation, sensitization, systemic toxicity and tissue reaction. Intra-arterial administration was performed in a swine model of hepatic arterial embolization in which 0.22–1 mL of sedimented bead volume was administered to the targeted lobe(s) of the liver. The beads could be visualized during the embolization procedure with fluoroscopy, DSA and single X-ray snapshot imaging modalities. CT imaging was performed before and 1 h after embolization and then again at 7, 14, 30 and 90 days. LC Bead LUMI™ could be clearly visualized in the hepatic arteries with or without administration of IV contrast and appeared more dense than soluble contrast agent. The CT density of the beads did not deteriorate during the 90 day evaluation period. The beads embolized predictably and effectively, resulting in areas devoid of contrast enhancement on CT imaging suggesting ischaemia-induced necrosis nearby the sites of occlusion. Instances of off target embolization were easily detected on imaging and confirmed pathologically. Histopathology revealed a classic foreign body response at 14 days, which resolved over time leading to fibrosis and eventual integration of the beads into the tissue, demonstrating excellent long-term tissue compatibility.